Engaging patients and families in communication across transitions of care: an integrative review protocol. (18th March 2016) - Bucknall, Tracey K.; Hutchinson, Alison M.; Botti, Mari; McTier, Lauren; Rawson, Helen; Hewitt, Nicky A.; McMurray, Anne; Marshall, Andrea P.; Gillespie, Brigid M.; Chaboyer, Wendy
Abstract: Aim: To describe an integrative review protocol to analyse and synthesize peer‐reviewed research evidence in relation to engagement of patients and their families in communication during transitions of care to, in and from acute care settings. Background: Communication at transitions of care in acute care settings can be complex and challenging, with important information about patients not always clearly transferred between responsible healthcare providers. Involving patients and their families in communication during transitions of care may improve the transfer of clinical information and patient outcomes and prevent adverse events during hospitalization and following discharge. Recently, optimizing patient and family participation during care transitions has been acknowledged as central to the implementation of patient‐centred care. Design: Integrative review with potential for meta‐analysis and application of framework synthesis. Review method: The review will evaluate and synthesize qualitative and quantitative research evidence identified through a systematic search. Primary studies will be selected according to inclusion criteria. Data collection, quality appraisal and analysis of the evidence will be conducted by at least two authors. Nine electronic databases (including CINAHL and Medline) will be searched. The search will be restricted to 10 years up to December 2013. Data analysis will include content and thematic analysis. Discussion: The review will seek to identify all types of patient engagement activities employed during transitions of care communication. The review will identify enablers for and barriers to engagement for patients, families and health professionals. Key strategies and tools for improving patient engagement, clinical communication and promoting patient‐centred care will be recommended based on findings.